744 THE USE OF IMMUNOFLUORESCENCE TO EVALUATE THE PERFUSION OF THE GASTRIC PLASTY DURING OESOPHAGECTOMY. (17th September 2021) - Abelló, David; Navío, Ana; Aguilar, Karen Stephanie; Avelino, Lourdes; Cholewa, Hanna; Mingol, Fernando; Bruna, Marcos; Vaqué, Javier; García-Granero, Eduardo
Abstract: : Anastomotic leakage in oesophageal cancer surgery is one of the most serious complications and occurs mainly at the cervical level between 10–30% according to series. The use of immunofluorescence could help to select a better vascularized area in which to perform the anastomosis more safely. We present the initial experience (between July and December 2020) of our group. Methods: Prospective and descriptive study of patients with oesophageal neoplasia who underwent a 3 stage oesophagectomy with cervical anastomosis using immunofluorescence with indocyanine green (dose: 7, 5 mg) for quick evaluation of vascularization in the theoretical anastomosis zone in gastric plasty. Intravenous injection of the indocyanine green dilution was performed intraoperatively in a peripheral line, once the plasty was positioned in place to perform the anastomosis. The route of ascent was transmediastinal in all cases. 9 patients with a mean age of 61 ± 7.6 years were included in the study. Results: The mean heart rate was 83 ± 16 bpm, the mean systolic blood pressure was 111 ± 17 mmHg. The time and mean speed it took for the fluorescence to reach the marked area to perform the anastomosis was 30 ± 28 seconds and 1.83 cm/sec; and at the apex of the plasty it was 93 ± 79 seconds and 0.75 cm/sec. In all patients in whom the anastomosis was performed in the area where ICG arrived between 30 and 90 seconds, there was no leakage. In two patients, due to anatomical needs, the anastomosis was performed in areas where ICG took more than 100 seconds and in the postoperative period leaked. Conclusion: Immunofluorescence is a technique that allows an immediate visual image to evaluate the vascularization of the gastric plasty during an esophagectomy. It allows characterizing the adequate vascularization of the future anastomotic area, being able to help decide the best place to carry out the anastomosis. Studies with a larger number of cases are needed to be able to define the range in which to establish the anastomosis or change the surgical strategy.